SOCIALIZATION OF THE PREVENTION OF SYMBOLIC VIOLENCE THROUGH THE SNAKES AND LADDERS GAME TO SMA 1 TELUK JAMBE STUDENTS IN KARAWANG REGENCY - Nursanti, Siti; Tayo, Yanti; Sulistyo, Nina; Dharta, Firdaus Yuni; Setyastuti, Yuanita; Syam, Syisea Putri; Asegaf, Ridwan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Symbolic violence is a form of violence that occurs through language, symbols, or actions that demean, discriminate, or exploit a person or group. Preventing symbolic violence can be done by increasing awareness about symbolic violence and its impact on society, respecting diversity and avoiding stereotypes that demean or discriminate against certain groups, encouraging critical thinking and self-reflection in individuals and groups to avoid actions or speech that can cause symbolic violence, develop policies that are inclusive and respect diversity in educational environments, workplaces and communities. For this reason, it is necessary to collaborate between service members who are lecturers at Singaperbangsa University Karawang and students of SMA 1 Teluk Jambe in Karawang Regency which aims to identify symbolic violence that occurs in society and socialize the Anti-Symbolic Violence Movement through the Snake and Ladder Game. By combining these approaches, it is hoped that it will be easier to identify symbolic violence and take steps to prevent and overcome the problem early on.